2018
DOI: 10.1016/j.cognition.2018.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition accumulates over time at multiple processing levels in bilingual language control

Abstract: It is commonly assumed that bilinguals enable production in their nondominant language by inhibiting their dominant language temporarily, fully lifting inhibition to switch back. In a re-analysis of data from 416 Spanish-English bilinguals who repeatedly named a small set of pictures while switching languages in response to cues, we separated trials into different types that revealed three cumulative effects. Bilinguals named each picture (a) faster for every time they had previously named that same picture in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
61
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(75 citation statements)
references
References 81 publications
7
61
2
Order By: Relevance
“…With a large group of Spanish-English bilinguals (cf. Kleinman & Gollan, 2016), Kleinman and Gollan (2018) recently showed that the occurrence of the reversed language dominance effect might be due to the number of trials. In their study, they found that the language dominance pattern reversed more as participants performed more trials, which indicates that it takes time to observe a reversed language dominance effect in a mixed language block.…”
Section: Markers Of Proactive Language Controlmentioning
confidence: 99%
“…With a large group of Spanish-English bilinguals (cf. Kleinman & Gollan, 2016), Kleinman and Gollan (2018) recently showed that the occurrence of the reversed language dominance effect might be due to the number of trials. In their study, they found that the language dominance pattern reversed more as participants performed more trials, which indicates that it takes time to observe a reversed language dominance effect in a mixed language block.…”
Section: Markers Of Proactive Language Controlmentioning
confidence: 99%
“…One criticism of the picture-word paradigm is that explicitly presenting distractor words makes lexical selection unlike what would occur normally (Finkbeiner et al, 2006; Spalek, Damian & Bölte, 2013). For example, the target word may receive an activation boost from the distractor because both the picture and the word activate the same semantic representation (Kleinman & Gollan, 2018). Translation distractors may also contribute to picture recognition speed (Hermans, 2000, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, as experimenters have tested task switching not just across block but also within block, they need to distinguish between global and local costs of switching, respectively [82] or, by another-yet-synonymous set of labels, switching costs and mixing costs, respectively [83]. Local/mixing costs may reflect that trial-by-trial variation in the task set never permits full reconfiguring the task set, and more global/switching costs may come from maintaining multiple tasks sets [82], but the costs of having to inhibit interfering task-stimulus relationships seem to accrue across time, no matter their source [84].…”
Section: Discussionmentioning
confidence: 99%